The Impact of Empowering Local Communities Through Food and Beverage Businesses at The Palo Naga Tourism Object, Deli Serdang Regency, North Sumatra Province - Suprapto, Yon; Syahrul, Syahrul; Masditou, Masditou; Syahfitri, Nova (Cattleya Darmaya Fortuna, 2024)
This study aims to determine the empowerment of local communities through food and beverage businesses at the Palo Naga tourist attraction, the effect of selling traditional food and drinks on increasing visitor interest in coming to the Palo Naga tourist attraction. This research is a quantitative descriptive research and the samples of this research are several food and beverage sellers and visitors of the Paloh Naga tourist attraction. The results of this study are that the management of the Palo Naga tourist attraction is very serious to guide the community, especially housewives in supporting the Palo Naga tourist attraction to sell in the tourist attraction area. All outlets are provided by the manager to be used as a place to sell free of charge and all sellers involved are from local residents. To improve the skills of these women sellers, the management often organizes training, both training on food processing and making souvenirs, in collaboration with some agencies by providing vocational homes as places for the training. The existence of the Palo Naga tourist attraction which utilizes the community's paddy fields besides having a cool natural and village feel as a visitor attraction, turns out to be a reason to enjoy the atmosphere and traditional food at this tourist attraction has a very strong influence on visitors coming. Most of the food and drinks are rather difficult to find in the city and the transaction system is also quite interesting where payments to sellers are not in cash, but using a medium of exchange made of wood.